Net migration and its skill composition in the Western Balkan countries between 2010 and 2019: Results from a cohort approach - Sandra M. Leitner (The Vienna Institute for International Economic Studies (wiiw), 2021)
In our analysis we applied the newly developed 'cohort approach' to the six Western Balkan countries (Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia and Serbia) for the period 2010-2019 to shed light on the total extent and skill composition of net migration, differentiating between four educational levels: Low (primary or lower secondary education), Medium-general (upper secondary general education), Medium-VET (upper secondary vocational education and training), and High (tertiary education). Our results show that during the period analysed all six countries experience net emigration. However, in terms of magnitude and particular age pattern these movements differ across countries. Net migration is particularly prevalent among the young. A high youth unemployment rate, family reunification and education abroad are key drivers behind this pattern. A further breakdown of net migration by highest level of education shows that net emigration in the region occurs mainly among the medium- and low-educated, particularly among those in their early to mid-20s and early 30s. There is evidence of brain drain in Albania, Bosnia and Herzegovina and Kosovo. In Albania, net emigration of the highly educated is substantial and accounts for almost 40% of the total estimated cumulative outflow. Brain drain in Albania and Kosovo is highest among recent university graduates. Importantly, and contrary to widespread perception, there is evidence of brain gain in some Western Balkan countries, namely in Montenegro, North Macedonia and Serbia. The key drivers of this are students, who return in large numbers to their home countries after graduating from tertiary education abroad. In Serbia and Montenegro immigration of highly skilled workers is also important in this context.
Keywords: J61; J24; 330; Net-migration; skill composition; Western Balkans; cohort approach